INOVASI PENGOLAHAN AMPAS KEDELAI MENJADI PUPUK ORGANIK CAIR UNTUK MENINGKATKAN PENDAPATAN PENGRAJIN TAHU TEMPE PADA MASA COVID DI DESA BATUMARTA I KECAMATAN LUBUK RAJA OKU (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2020)
Soybean dregs processing innovation is an innovation offered to tofu craftsmen partners in Batumarta I Village, Lubuk Raja Subdistrict, OKU Regency to increase their income during the Covid pandemic. Tofu production activities in this village every day produce waste in the form of dregs. Soybean dregs are usually often thrown away or used as animal feed. To produce additional content for tofu craftsmen, the dregs are reprocessed into commercially valuable snacks, for example liquid organic fertilizer (POC). Liquid Organic Fertilizer (POC) is a new business option that can provide more profit for tofu craftsmen in Batumarta I. Since entering the covid pandemic, many businesses have been affected, which has reduced sales turnover, including tofu making efforts. The solution given to tofu craftsmen is through processing the waste into other processed products that can be sold for profit, one of which is carir organic fertilizer. Processing of soybean dregs left over from making tofu can be a mainstay product with commercial value. Apart from generating profits, this business helps tofu craftsmen in handling their waste to create an environmentally friendly industry. The method used in this case is through assistance in the form of processing soybean dregs into POC. The solutions provided are also through business management training, digital-based marketing for POCs in order to attract market attention. The POC soybean dregs processing technology will create a new business that can become the mainstay product of Batumarta I Village. With attractive packaging and online marketing, it is hoped that it will be able to increase the income of tofu craftsmen, especially during the Covid pandemic.